Toxicity effects of zinc on two marine diatoms, under varying macronutrient environment. (November 2018) - Anu, P.R.; Bijoy Nandan, S.; Jayachandran, P.R.; Don Xavier, N.D.; Midhun, A.M.; Mohan, D.
Abstract: Diatoms constitute one of the fundaments in the trophic food chains and are responsible for much of the bioaccumulation of heavy metals, in particular zinc, throughout the web of food chains. Chaetoceros calcitrans and Thalassiosira weissflogii are widely present as a dominant marine diatom in estuarine and coastal waters. The zinc uptake, its fractionation in subcellular structures and macromolecular compartments in two marine diatoms, C. calcitrans and T. weissflogii and trophic transfer under different macronutrient concentrations were investigated. The study reveals a significant interaction between macronutrients and metal uptake by the two diatom species. Increased cellular accumulation of zinc and N, P-limited condition were found to affect N, P and Si assimilation by diatoms negatively. Conversely, nitrogen (N) limitation inhibited the intracellular uptake of zinc. However, at higher concentration of zinc, the difference in zinc uptake between nutrient enriched condition (+NP) and nutrient limited (N or P) condition become smaller, indicating that the zinc uptake by diatoms is less dependent on N containing protein ligands at high Zn concentration. Nitrogen concentration in the medium was also found to affect the relative distribution of zinc in subcellular structures and macromolecular components. However, major portion of zinc was distributed in soluble substance and in the protein of the algal cells. The N limited condition facilitates the accumulation of zinc in cell organelles (insoluble substance) leading to increased toxicity. Trophic transfer of zinc was also measured by calculating percentage of metal retained in mussel, Perna viridis over the experiment period. Regardless of the algal species, the percentage of accumulation of zinc was found to be high in mussels fed with algal cells acclimated to nutrient enriched condition (31 and 38%). Our study therefore suggests that N enrichment may lead to an increase in Zn uptake and transfer in marine plankton. Highlights: Ambient N concentration plays a pivotal role in uptake of Zn in C. calcitrans and T. weissflogii . Increased cellular accumulation of zinc and N/P-limited condition negatively affect N, P and Si assimilation by diatoms. Zinc uptake by diatoms is less dependent on N containing protein ligands at high Zn concentration. Varying nutrient condition affects the Zn distribution in the subcellular compartments and macromolecular structures. Nutrient enrichmnt may lead to an increase in zinc uptake and trophic transfer along the food chain.